HUBUNGAN ANTARA KONTROL DIRI DENGAN PERILAKU MENYONTEK PADA SISWA KELAS X SMA NEGERI 3 PEMALANG - Nela Agistiani; Tri Suyati; G. Rohastono Ajie (CV. Denasya Smart Publisher, 2024)
This research was motivated by students' low self-control. One of the causes of students engaging in cheating behavior is students' low self-control. The formulation of the problem in this research is, is there a relationship between self-control and cheating behavior in class X students at SMA Negeri 3 Pemalang?